2018
DOI: 10.1016/j.jesp.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The interpersonal effects of emotions in money versus candy games

Abstract: Emotional expressions significantly influence perceivers' behavior in economic games and negotiations. The current research examined the interpersonal effects of emotions when such information cannot be used to guide behavior for increasing personal gain and when monetary rewards are made salient. For this, a one-shot Public Goods Game (Studies 1, 2, and 3) and Dictator Game (Studies 4 and 5) were employed, in which the dominant strategy to maximize personal payoff is independent from the counterplayers' inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 74 publications
1
18
0
1
Order By: Relevance
“…For example, after United CEO Oscar Munoz’s written apology for a violent passenger reaccommodation was perceived as insufficiently emotional, United stock lost 4% of its value (Kottasova, 2017). Similarly, prior research finds that emotion (mis)perception influences cooperation, conflict, and even task performance (Wang et al, 2018; Wubben et al, 2009).…”
Section: Emotion Perception In Text-based Communicationmentioning
confidence: 77%
“…For example, after United CEO Oscar Munoz’s written apology for a violent passenger reaccommodation was perceived as insufficiently emotional, United stock lost 4% of its value (Kottasova, 2017). Similarly, prior research finds that emotion (mis)perception influences cooperation, conflict, and even task performance (Wang et al, 2018; Wubben et al, 2009).…”
Section: Emotion Perception In Text-based Communicationmentioning
confidence: 77%
“…One of the reasons for the current result is that IGT generally uses monetary feedback. Wang et al (2018) found that emotional expressions influence the behavior of the observer when candy is used as feedback in an economic game, but when money is targeted, those effects disappear. Monetary feedback and a similar framework may make participants more self-centered and less sensitive to social information, such as facial expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Even an intuitive concept like fairness can be interpreted in multiple ways: for example, through the principle of equality (each gets an equal share), the principle of equity (benefits should be distributed in proportion to an individual’s investment), or the principle of need (benefits should go to those with greatest need). Personality and culture shape which principles a person will tend to adopt (Stouten, de Cremer, and van Dijk 2005), and the same person might evoke different principles in different situations (Wang, Krumhuber, and Gratch 2018). Moreover, the concept of fairness itself can be negotiated—individuals may change their principles in response to arguments or to knowledge about the norms of others (Fehr and Gächter 2000).…”
Section: Automated Negotiators As Proxiesmentioning
confidence: 99%